Echocardiography in the CCU (Springer International Publishing, 2018)
This book comprehensively reviews the use of echocardiography in the rapidly evolving field of critical care cardiology. Increasingly, cardiac care units (CCU) are focusing on the management of patients with multisystem diseases, advanced hemodynamics compromise, complex ventricular arrhythmias, and established or incipient multi-organ failure. This book covers ultrasound applications in such topics as hemodynamic assessment and the assessment of patients with intracardiac devices. Syndrome-based echocardiography in the CCU is also covered with an emphasis on using echocardiography in patients with acute dyspnea, acute chest pain and neurologic syndromes. The use of contrast echocardiography in the CCU is also covered. Echocardiography in the CCU reveals the essential role of various echocardiographic modalities in modern acute cardiovascular care. This is therefore a critical resource for all cardiology practitioners and trainees who use echocardiography in CCUs.